Investigating the Use of ICT in Literature Classrooms A Case Study of Master in the Department of English at Laghouat University - GOURID,Nassima; GUETTAF,Zineb; MHAMEDI ,Nadir (University of Ammar Theledji -Laghouat, 2020)
Formal teaching of literature requires a close examination of the teaching aids. The current study aims at investigating the usage of ICT in literature classes. Such an investigation subsumes the exploration of the way technology is deployed and the students’ attitudes towards it. The study sheds light on the probabilistic limitations facing the ideal implementation of an ICT-assisted approach to teaching literature. The methodological framework developed for the present study makes use of the mixed-method descriptive approach where a sample of 40 male and female students of master are chosen from the department of English at Ammar Thelidji University. A questionnaire of 13 items is administred online in order to collect the data necessary to attend to the research questions. The findings, by and large, suggest that there is an acute lack in the integration of computer-assisted teaching materials from the part of the teachers. The students, on th econtrary, show a more frequent use of ICT in managing their learning outcomes